Awareness and Application of Artificial Intelligence Tools in Prosthodontic Treatment Planning Among Dental Students and Practitioners in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2026)
Introduction: Artificial intelligence (AI) is increasingly utilized in dentistry to enhance diagnostic accuracy and treatment planning. In prosthodontics, AI tools have shown considerable potential in improving precision and efficiency; however, their awareness and clinical adoption among dental students and practitioners in Saudi Arabia remain limited. Objectives: This study aims to assess the awareness, knowledge, and application of AI tools in prosthodontic treatment planning among dental students and practitioners in Saudi Arabia. Methodology: A cross-sectional survey was conducted between July and December 2025 using a self-administered online questionnaire distributed through university channels and professional dental platforms. Participants included clinical dental students, interns, general dentists, and prosthodontic specialists actively practicing in Saudi Arabia. Preclinical students and non-prosthodontic practitioners were excluded. A minimum sample size of 384 was calculated, with a target of 422 to compensate for nonresponse.